Multicolour photometric study of pulsations in a pre-main sequence star V351 ORI (HD38238) - Ayane, Getinet Feleke (North-West University (South Africa), 2013)
"Abstract not copied"
MSc (Agriculture), North-West University, Mafikeng Campus, 2013